Remote and Radar Investigation of the Left Irbistu Glacier (South Chuisky Mountain Range, Altai Republic) - O. V. Ostanin; S. A. Kobylin; G. S. Dyakova; R. D. Burym; A. D. Patrusheva; N. E. Ramazanova (Лëд и снег)
To determine changes of glacier No. 31 (SU5A15106031), happened in the beginning of the XXI century, satellite images, obtained from the Landsat-7, 8, 9 and Sentinel-2 satellites in different years, were analyzed. As a result, data on the glacier changes were obtained for the period from 2000 to 2022. During this time, the length of the main stream of the glacier decreased by 144 m (6.8%), and the total area of the entire glacier – by 0.089 km2 (9.7%). The rate of retreat of the glacier front varied from 2 to 15 m/year, on average – 6.5 m/year, and the glacier area decreased by on average of 0.004 km2/year. In 2022, the glacier consisted of two separate ice streams, with a total area of 0.823 km2 and a maximum length of 1.955 km. Aerial photography was carried out using a DJI Phantom 4 quadcopter. A high-resolution orthophotoplan (±5 cm), a digital terrain model, a three-dimensional model of the surface of the glacier tongue and adjacent territories, with a total area of 0.25 km2, were made. Radar sounding was performed by the Python-3 georadar in two configurations: at frequencies 50 and 100 MHz. Two cross-sections of the glacier were constructed from the radar data: one was taken at a frequency of 100 MHz, and the second at both – 50 MHz and 100 MHz. The analysis of the radiogram of these profiles made possible to reveal that the larger thickness of the glacier in the study area was measured along the left side of the glacier tongue, the maximum recorded thickness was equal to 66 m